PENAJAMAN CITRA REMOTE SENSING MENGGUNAKAN METODE FILTERING DI AREA PEMBUDIDAYAAN RUMPUT LAUT - Muhammad Sesio Dhia Ramadhan; Nuryuliani Nuryuliani; Lulu C Munggaran; Elfitrin Syahrul (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
Abstract : Indonesia has excellent natural potential for seaweed industry. To help farmers understand the harvest period, an application needs to be built. In this research, a preprocessing application for processing seaweed image processing is taken through remote sensing. Preprocessing is using the Unsharp Mask Filtering and Laplacian Filtering methods. The performace metrics results using the SSIM method show that Laplacian level 2 filtering method gives better result.